2014
DOI: 10.1089/ten.tea.2012.0613
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Burst Pressure: Initial Evaluation of the Natural History of the Biaxial Mechanical Properties of Tissue-Engineered Vascular Grafts in the Venous Circulation Using a Murine Model

Abstract: We previously developed and validated a murine model for investigating neotissue formation in tissueengineered vascular grafts (TEVGs). Herein, we present the first longitudinal assessment of both the microstructural composition and the mechanical properties of a TEVG through the process of neovessel formation (total scaffold degradation). We show that when (poly)glycolic acid-based biodegradable scaffolds were used as inferior vena cava interposition grafts in mice, the evolving neovessel developed biaxial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 28 publications
5
52
0
Order By: Relevance
“…Prior constitutive relations were augmented to incorporate (i) the monotonic loss of a load-bearing polymeric scaffold over time and, in the latter case, (ii) an additional inflammatory-mediated production of matrix that precedes the typical mechanomediated production. Of particular importance herein, the model of Miller et al [35] described well the experimentally observed evolving mechanical behaviors of TEVGs implanted in the murine inferior vena cava [5]. Here, we extended this model of in vivo neovessel development to consider parametrically the roles of scaffold physical parameters on TEVG evolution via their effects on the kinetics of matrix production and removal during both the early inflammatory phase and the subsequent mechano-mediated phase.…”
Section: Computational Modelmentioning
confidence: 78%
See 2 more Smart Citations
“…Prior constitutive relations were augmented to incorporate (i) the monotonic loss of a load-bearing polymeric scaffold over time and, in the latter case, (ii) an additional inflammatory-mediated production of matrix that precedes the typical mechanomediated production. Of particular importance herein, the model of Miller et al [35] described well the experimentally observed evolving mechanical behaviors of TEVGs implanted in the murine inferior vena cava [5]. Here, we extended this model of in vivo neovessel development to consider parametrically the roles of scaffold physical parameters on TEVG evolution via their effects on the kinetics of matrix production and removal during both the early inflammatory phase and the subsequent mechano-mediated phase.…”
Section: Computational Modelmentioning
confidence: 78%
“…Here, we extended this model of in vivo neovessel development to consider parametrically the roles of scaffold physical parameters on TEVG evolution via their effects on the kinetics of matrix production and removal during both the early inflammatory phase and the subsequent mechano-mediated phase. Selected constitutive relations and model parameters were informed by longitudinal data on cell biological, histological, and mechanical changes in a murine inferior vena cava (IVC) interposition TEVG studied for 24 weeks as well as related data from the native murine IVC [4,5,32,40,41]. Given a lack of detailed information on initial and evolving changes in polymer fiber alignment within the TEVG (as well as insufficient data to formulate illustrative constitutive functions relating alignment with the host inflammatory response and TEVG mechanical properties), however, we focused on effects due to porosity and fiber diameter, namely false(ε,ωritalicminfalse) for the non-woven scaffold used.…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical stress applied during the conditioning phase has been demonstrated to support the maturation of TEBV and may reduce the potential risk of failure in vivo. Vessel stretching through pulsation improves mechanical properties, such as ultimate tensile strength and modulus [56][57][58][59][60][61], as well as enhances SMC proliferation and ECM remodeling [62,70,71].…”
Section: Conditioning Approachesmentioning
confidence: 99%
“…[8][9][10] Simultaneously engrafted macrophages and fibroblasts in the scaffold deposit extracellular matrix (ECM) precursors (MMP-2, MMP-9) that over time result in the formation of a robust and organized vascular ECM that determines the mechanical characteristics of the TEVG. 11,12 The degree of macrophage infiltration has been shown to correlate with the incidence of stenosis, and one role of bone marrow mononuclear cell seeding is to mitigate the host's initial foreign body response to the scaffold, thereby preventing acute stenosis and promoting tissue regeneration. 9 Interestingly, patent TEVGs in a C57BL/6 model have been reported without the use of cell seeding; however, the incidence of neointimal hyperplasia and stenosis in unseeded (cell-free) TEVGs after 2 weeks of implantation is high (64%).…”
Section: Introductionmentioning
confidence: 99%